The strategic interplay between the low-cost carrier industry and Singapore's Integrated Resorts - Choo, Suling (2008)
This paper seeks to explore in-depth the interdisciplinary relationship between the Low Cost Carriers (LCCs) and the proposed Integrated Resorts (IRs), highlighting insights and recommendations to boost regional market share and tourism expenditure of Singapore. The discussion is based on data extracted from Asian regions served by LCC, together with trends in the regional LCC and IR industries.